Unethical Leadership and Organizational Culture: Contributing Factors to FTX’s Collapse - Krishnan, Varadharaj Varadhan (Journal of Global Economy, Business and Finance, 2025)
The leadership of a company plays a significant role in influencing its culture. It determines the long-term success or failure of the organization. Ethical leadership is crucial in establishing a healthy organizational culture. Unethical leadership may lead to the downfall of promising or even successful businesses. This paper examines the case of Sam Bankman-Fried, whose unethical leadership and Machiavellian behavior contributed to the collapse of FTX and Alameda Research, leading to bankruptcy and legal consequences. The study also highlights the importance of fostering an ethical culture through strong leadership, a robust ethics and compliance pro- gram, and sound business practices by analyzing the culture and leadership failures in these companies. The insights from this study can guide business leaders to avoid legal and reputational damage caused by unethical leadership and ensure sustainable success for their organizations.